Getting What You Pay For: Children's Use of Market Norms to Regulate Exchanges. Issue 6 (11th May 2018) - Echelbarger, Margaret; Gelman, Susan A.; Kalish, Charles W.
Abstract : Children are sensitive to a number of considerations influencing distributions of resources, including equality, equity, and reciprocity. We tested whether children use a specific type of reciprocity norm—market norms—in which resources are distributed differentially based strictly on amount offered in return. In two studies, 195 children 5–10 years and 60 adults distributed stickers to friends offering same or different amounts of money. Overall, participants distributed more equally when offers were the same and more unequally when offers were different. Although sensitive to why friends offered different amounts of money, children increasingly incorporated market norms into their distributions with age, as the oldest children and adults distributed more to those offering more, irrespective of the reasons provided.